On the Development Perspectives of the Kazakhstan Agro-sector - KANTARBAYEVA, Shyryn M.; KAIYRBAYEVA, Ainur Ye.; RAKHIMZHANOVA, Gaukhar M.; MYKHYBAYEV, Maxat S. (Journal of Advanced Research in Law and Economics; Vol 11 No 2 (2020): JARLE Volume XI Issue 2(48) Spring 2020, 2020)
The development of the economy in Kazakhstan is associated with the production level and economic growth in the agricultural sector. This attracts the attention of countries willing to invest in the agro-industrial sector of the republic. At the same time, it should be understood that much depends on the conditions that have been developed in the production and export of agricultural products and provisions. The development of the agrarian economy of the republic is greatly influenced by the development of this sphere in the nearest partner countries in political, economic and trade relations, such as Russia, Belarus and China. Within the initiative to revive the Silk Road, the Celestial Empire has a significant impact on the development prospects of Kazakhstan, including agrarian economy as well.